Portrayal of Postcolonial Afghanistan and Postcolonial Themes of Identity, Displacement and Cultural Conflict in the Kite Runner - Saeed, Najwa Mohammed; Saeed, Baleid Taha Shamsan (مجلة العلوم التربوية والدراسات الإنسانية سلسلة الآداب والعلوم التربوية والإنسانية والتطبيقية, 2025)
This study intends to provide a compendium of academic analyses regarding the post-colonial interpretation of Khaled Hosseini's The Kite Runner. This indicates that identity, trauma, cultural tensions, and concerns are confronted by the diverse critics of the diaspora. These reviewers argued that class, gender, and ethnic identity concerns in Afghanistan are pertinent to the themes of exile and belonging in The Kite Runner. The anthology encompasses diverse perspectives-cultural, political, and historical - on The Kite Runner, in addition to an extensive discourse on postcolonial theory and literature. This study utilises a qualitative research methodology grounded in literary analysis and postcolonial theory, employing thematic analysis to investigate identity, displacement, and cultural conflict in the novel. The context for these works is intrinsically varied and stems from distinct critical approaches and viewpoints, defining the extensive discourse surrounding Hosseini's narratives in modern literary criticism. The findings of this study illustrate how colonial and postcolonial conflicts fragment identity, with displacement reshaping characters' senses of self and belonging. The novel depicts Afghanistan as culturally fractured, where class and ethnic divisions, especially between Pashtuns and Hazaras, reflect deep colonial legacies. The diasporic experience intensifies internal conflicts around identity, guilt, and cultural dislocation, particularly through Amir's character. Hosseini's work not only narrates personal redemption but also engages with broader postcolonial struggles, making it a rich text for exploring the intersections of history, culture, and literature.